Risk factors for steroid-refractory in immune checkpoint inhibitor-induced colitis: a retrospective cohort study - Meng, Ke; Chen, Jing; Chen, Junzhe; Sun, Shengjie; Li, Hui; Zhou, Guanzhou; Pan, Fei (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) represent an effective treatment for various malignant tumors. However, the utilization of ICIs is frequently accompanied by immune-related adverse events (irAEs), among which immune checkpoint inhibitor (ICI)-induced colitis is a notable complication. Current clinical guidelines recommend corticosteroids as the first-line therapy for ICI-induced colitis. Nevertheless, subset of patients fails to respond adequately to corticosteroid therapy, resulting in steroid refractoriness. At present, studies investigating the risk factors for steroid-refractory remain limited.Patients and methodsA retrospective analysis was conducted on patients diagnosed with ICI-induced colitis after malignant tumor treatment with ICIs. Data collected included demographics, tumor and ICIs types, time to colitis onset, number of ICIs treatments, clinical manifestations (diarrhea, abdominal pain, bloody stool, fever), endoscopic findings (ulcerative lesions, extent of lesion distribution), laboratory results, grades of diarrhea and colitis, and corticosteroid treatment response. Patients were stratified into steroid-responsive and steroid-refractory groups. Multivariate logistic regression analysis was employed to identify risk factors related to steroid-refractory. Kaplan-Meier survival analysis and log-rank tests were conducted to compare survival time differences between the two groups.ResultsA total of 57 patients were included, with 45 patients in the steroid-responsive group and 12 patients in the steroid-refractory group. Univariate analysis revealed differences between the two groups in the time to colitis onset (median days: 97 vs. 141, P = 0.037), presence of fever (4.4% vs. 25.0%, P = 0.045), presence of ulcerative lesions (26.9% vs. 34.6%, P = 0.036), grades of colitis (P = 0.011), and serum interleukin-6 (IL-6) level (24.1 ± 20.5 pg/mL vs. 81.7 ± 38.7 pg/mL, P < 0.001). Multivariate regression analysis indicated that serum IL-6 level was an independent risk factor for steroid-refractory. Kaplan-Meier survival analysis showed no significant difference in survival time between the two groups.ConclusionsFor patients with ICI-induced colitis, serum IL-6 level at colitis onset could serve as an independent risk indicator for predicting the efficacy of corticosteroid therapy. Early consideration of selective immunosuppressive therapy (SIT) may be warranted with caution for patients with high serum IL-6 level.